Relationship between performance of gymnastic elements and national cup success in older youth categories of alpine skiing - Šuc, N.; Weissenstein, M.; Lešnik, B. (Science of Gymnastics Journal, 2018)
Competitive alpine skiing and gymnastics belong to polystructural sports disciplines. One of the differences between them are the conditions under which they are implemented. The external conditions in gymnastics are constant, in alpine skiing they vary. Due to the wide impact of gymnastics on the development of motor skills, this discipline is used as a means of physical preparation of young alpine skiers. The aim of this study was to determine whether there is a connection between the selected gymnastic elements and competitive performance of young alpine skiers, aged 14 to 15. The sample of variables consisted of eight tests about of gymnastic elements and an overall assessment. The independent variable represented the points scored in the cup for the Mercator Grand prize. The sample consisted of 34 athletes, 22 boys and 12 girls, all of them were competing that season. Considering the results, we can say that the relationship between competitive performance in alpine skiing is statistically typical for the group of boys, but not girls. In the group of boys, the statistically significant predictors of prosperity in alpine skiing were proven to be four of gymnastic elements and the total score of gymnastic elements, whereas in the group of girls only one element proved to be a statistic predictor. Differences in ranking positions influence gymnastic elements scores on performance success at competitions is statistically significant in older boys at a 5% risk level, whereas in the older girls category overall gymnastic elements do not influence total performance.